2021
DOI: 10.4103/jfmpc.jfmpc_2417_20
|View full text |Cite
|
Sign up to set email alerts
|

Drug utilization pattern and factors associated with polypharmacy and excessive polypharmacy in geriatric medical out-patients at a rural health training centre in India

Abstract: Context: Multiple chronic illnesses associated with ageing population demands the role of polypharmacy. Drug utilization study in terms of description of drug use pattern in the geriatric patients aids in monitoring polypharmacy as well as to determine the factors contributing to it. Objectives: To analyse the drug utilization pattern in geriatric patients at a rural health training centre. Subjects and Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 6 publications
1
7
1
Order By: Relevance
“…Fifty studies focussed on education [16, 18, Fig. 1 Study selection and exclusion according to the PRISMA flow diagram 20-67], 18 studies on income [16, 23, 30, 32-34, 37, 41, 46-48, 50, 53, 61, 63, 64, 66, 68], 6 on wealth [22,27,45,57,67,69], 4 studies on occupation [23,44,48,57], 7 studies on employment [16,17,49,58,60,63,66], 5 studies on social class [17,25,36,38,60], 2 used SES categories [31,70] and 1 used area-level deprivation [20]. Studies were conducted across a range of countries as follow: India [60,66], Jordan [21], Netherlands [70], Sweden [18,23,39,52], Spain [25], Belgium [26,30], Pakistan [29,68], UK [17,20,36,38,69], China …”
Section: Study Characteristicsmentioning
confidence: 99%
See 4 more Smart Citations
“…Fifty studies focussed on education [16, 18, Fig. 1 Study selection and exclusion according to the PRISMA flow diagram 20-67], 18 studies on income [16, 23, 30, 32-34, 37, 41, 46-48, 50, 53, 61, 63, 64, 66, 68], 6 on wealth [22,27,45,57,67,69], 4 studies on occupation [23,44,48,57], 7 studies on employment [16,17,49,58,60,63,66], 5 studies on social class [17,25,36,38,60], 2 used SES categories [31,70] and 1 used area-level deprivation [20]. Studies were conducted across a range of countries as follow: India [60,66], Jordan [21], Netherlands [70], Sweden [18,23,39,52], Spain [25], Belgium [26,30], Pakistan [29,68], UK [17,20,36,38,69], China …”
Section: Study Characteristicsmentioning
confidence: 99%
“…Four studies [23,44,48,57] reported the association between occupation and polypharmacy, and 7 [16,17,49,58,60,63,66] reported the association between employment and polypharmacy. Three studies [23,44,57] assessing occupation and 5 studies [17,58,60,63,66] Fig.…”
Section: Association Between Occupation Employment and Polypharmacymentioning
confidence: 99%
See 3 more Smart Citations